Percutaneous CT-Guided Core Needle Biopsies of Head and Neck Masses: Technique, Histopathologic Yield, and Safety at a Single Academic Institution - Hillen, T.J.; Baker, J.C.; Long, J.R.; Friedman, M.V.; Jennings, J.W. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: CT-guided head and neck biopsies can be challenging due to the anatomy and adjacent critical structures but can often obviate the need for open biopsy. A few studies and review articles have described approaches to biopsy in the head and neck. This retrospective study evaluated technical considerations, histopathologic yield, and safety in CT-guided head and neck core needle biopsies.MATERIALS AND METHODS: A retrospective review of head and neck biopsies performed from January 2013 through December 2019 was conducted. Clinical diagnosis and indication, patient demographics, mass location and size, biopsy needle type, technical approach, dose-length product, sedation details, complications, diagnostic histopathologic yield, and the use of iodinated contrast were recorded for each case.RESULTS: A total of 27 CT-guided head and neck core needle biopsies were performed in 26 patients. The diagnostic sample rate was 100% (27/27). A concordant histopathologic diagnosis was obtained in 93% (25/27) of cases. There was a single complication of core needle biopsy, a small asymptomatic superficial hematoma.CONCLUSIONS: Percutaneous CT-guided biopsy of deep masses in the head and neck is safe and effective with careful biopsy planning and has a high diagnostic yield that can obviate the need for open biopsy.CTCAECommon Terminology Criteria for Adverse Events